PENGARUH PEMBERIAN MINYAK ATSIRI TEMULAWAK (Curcuma xanthorrhiza Roxb.) TERHADAP NAFSU MAKAN TIKUS YANG DITEKAN NAFSU MAKANNYA - , FAUZIA NURUL IZZATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In empirical side, temulawak is known having effect of increasing appetite so it used in jamu cekok for increasing appetite. Compound expected responsible for the effect is essential oil. In previous research, essential oil of temulawak proved can increase body weight in normal mice. This research was done to identify effect of temulawak essential oil and its optimal dosage in increasing appetite on pressed-appetite mice. Essential oil was obtained from vapor-water distillation of fresh temulawak rhizome. This research used diethylpropion HCL as appetite pressure and negative control. There are 7 test group including oil control, distilled water control, negative control (diethylpropion HCL with dosage of 1.35 mg), positive control (olanzapine with dosage of 0.18 mg), essential oil of 20 mg/kg bw, 40 mg/kg bw, and 80 mg/kg bw. Test was done for 28 days with three parameters which are the increase in body weight, food and beverage intake. The three parameters were calculated using AUC total of body weight and cumulative feed and drink. Data was analyzed with one-way ANOVA test and LSD post hoc test. The result indicated that essential oil with 20 mg/kg bw dosage can increase body weight of mice with pressed appetite significantly than negative control.